2020
DOI: 10.3126/pjri.v2i0.33431
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Skill and Motivation in Using Information and Communication Technology

Abstract: Teaching and learning in the 21st century has been embedded with technology. Use of Information and Communication Technology (ICT) plays a crucial role in ameliorating knowledge acquisition in general and enhancing English Language mastering in particular. The government of Nepal has made provision of integrating ICTs in school education to enhance quality education and make both teachers and learners confident and competitive in the present global world. The teachers are the real implementers of the policy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The results show that teachers' motivation, confidence, and skills and knowledge in using ICTs in the classroom are the major challenges as social constructivist approach claims motivation and active participation are the keys to success and knowledge is created gradually in the social context (Tinio, 2002;Pritchard & Woollard, 2010). The finding contrasts with the claim that teachers' motivation, skills, attitudes, opinions and their confidence on using ICTs in the language teaching are the effective measure of the success (Paudel, 2021;Schulz et al, 2015). Since teachers are the main actors for effective ICT adoption and use in the classroom, their poor skills and knowledge in handling ICT tools and modern computer based applications leads the programme to be failed.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The results show that teachers' motivation, confidence, and skills and knowledge in using ICTs in the classroom are the major challenges as social constructivist approach claims motivation and active participation are the keys to success and knowledge is created gradually in the social context (Tinio, 2002;Pritchard & Woollard, 2010). The finding contrasts with the claim that teachers' motivation, skills, attitudes, opinions and their confidence on using ICTs in the language teaching are the effective measure of the success (Paudel, 2021;Schulz et al, 2015). Since teachers are the main actors for effective ICT adoption and use in the classroom, their poor skills and knowledge in handling ICT tools and modern computer based applications leads the programme to be failed.…”
Section: Discussionmentioning
confidence: 87%
“…Rana and Rana (2020) conclude that teachers of the old generation have limited ICT knowledge and skills which may lead them to escape from using it. Paudel (2021) from his research found strong motivation of English teachers in applying ICTs even they lack confidence, adequate training, skills, and knowledge on them. All these accounts echo the need of exploring what opportunities motivate them in using ICTs despite their short understanding of ICT.…”
Section: Structure Of Education and Ict Policies In Nepalmentioning
confidence: 99%
“…This is in line with Cruthaka and Pinngern, [37], which note that providing lecturers with the appropriate training skills should help increase their technology competencies. However, Paudel [36] also assert that continuous ICT training is essential to help teachers keeping up with the development of ICT skills. The study is also in agreement with Chibueze et al [30] which states that the technical vocational education and training lecturers required digital skills for enhancing classroom instructional delivery as well as assessment of classroom instruction.…”
Section: Research Question 1: What Are the Views Of Vocational Educat...mentioning
confidence: 99%
“…So, for these skills to develop, teachers need to go through training programmes that help them gain knowledge, skills, and good attitudes. These programmes are made possible by integrating technology well into their roles and responsibilities [36]. Furthermore, the study show that teachers' low level of ICT usage is attributed to a lack of training [30], [37].…”
Section: Introductionmentioning
confidence: 99%